2010
DOI: 10.1007/978-3-642-13858-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Privacy Preserving Authentication for RFID Using a Stream Cipher

Abstract: Abstract. In this paper, a privacy preserving authentication protocol for RFID that relies on a single cryptographic component, a lightweight stream cipher, is constructed. The goal is to provide a more realistic balance between forward privacy and security, resistance against denial of service attacks, and computational efficiency (in tags and readers) than existing protocols. We achieve this goal by solely relying on a stream cipher-which can be arbitrarily chosen, for instance a stream cipher design aimed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Moreover, we implicitly assume that the evaluation time of F is greater than the time needed to sample (n) random bits. 9 [9] only states, and proves, the adaptive case, but the very same lines also yields the non-adaptive case. 10 Recall that for a set S and an integer t, S ≤t denotes the set {s ∈ S * :…”
Section: Definition 28 (Pseudorandom Functions Secure Against Many-omentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, we implicitly assume that the evaluation time of F is greater than the time needed to sample (n) random bits. 9 [9] only states, and proves, the adaptive case, but the very same lines also yields the non-adaptive case. 10 Recall that for a set S and an integer t, S ≤t denotes the set {s ∈ S * :…”
Section: Definition 28 (Pseudorandom Functions Secure Against Many-omentioning
confidence: 70%
“…Lemma 2.9 (cf., [9], Theorem 1). Let F = {F n : {0, 1} m(n) → {0, 1} (n) } n∈N be a function family ensemble.…”
Section: Definition 28 (Pseudorandom Functions Secure Against Many-omentioning
confidence: 98%
“…Also note that the honest communication between the reader and tag must be executed after the anonymous communication phase is finished. Billet, Etrog and Gilbert formalized the forward privacy model such that the honest execution occurs before the anonymous communication [3]. However, their model is not achievable since such a honest execution is useless and does not prevent any of the attacks described in Section 4 (Specifically, their proposed protocol PEPS falls into a type 2a protocol and does not satisfy their privacy model).…”
Section: Definition 5 An Rfid Authentication Protocol π Satisfies Thmentioning
confidence: 99%
“…A , -secure PRNG represents that the output of this PRNG cannot be discriminated with a true random string in time with advantage at most . The PRNG can be implemented using stream ciphers such as those proposed in the STREAM project (Cid & Robshaw, 2009) and a secure stream cipher is seen as a PRF (Billet et al, 2010). Definition 3.…”
Section: Mathematical Definitions Definition 1 Lpn Problemmentioning
confidence: 99%
“…Ma et al (2009) prove that the unpredictable privacy notion (Ha et al, 2008) is stronger than the indistinguishable privacy notion (Juels & Weis, 2007), and that the unpredictable privacy notion is equivalent to a pseudo random function (PRF). It can be observed that the majority of existing forward privacy schemes (Ohkubo et al, 2003;Berbain et al, 2009;Billet et al, 2010) are based on the indistinguishable privacy notion, and the F-HB protocol is based on the unpredictable privacy notion. Scalability must also be considered in forward private protocols based on symmetric-key ciphers.…”
mentioning
confidence: 99%